Mafhūm Ahl al-Sunnah wa al-Jamā’ah ‘Inda Jam’īyah Nahḍah al-‘Ulamā’ - Mohammad Tolchah Hasan (Studia Islamika, 2005)
this article deals with one of the basic pillars of traditionalist Islam in Indoneisa, ahlussunah waljama'ah (Ar. ahl al-sunnah wa al-jama'ah, meaning people of the sunnah and the [orthodox] community). it was first advocated in Indonesia by the leading 'ulama of the pesantrens, and then appeared as a key religious principle for Nahdlatul Ulama (NU), an institution of 'ulama in Indonesia established in 1926.DOI: 10.15408/sdi.v12i1.648